FENOMENA CASHLESS SOCIETY DI INDONESIA: ANALISIS DESKRIPTIF PERKEMBANGAN DAN DAMPAKNYA TERHADAP PERILAKU KONSUMEN - Aulia Rachel; Muhammad Yazid (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2026)
The rapid development of digital technology has encouraged significant changes in the payment system in Indonesia, leading to the emergence of a cashless society. Non-cash payment systems allow people to conduct transactions more quickly, practically, and efficiently through various instruments such as electronic cards, digital wallets, mobile banking, and QRIS. This study aims to analyze the development of the cashless society phenomenon in Indonesia and describe its impact on consumer behavior. This research uses a descriptive method with a literature study approach. The data used are secondary data obtained from various scientific journals, official reports, and relevant literature related to digital payment systems and consumer consumption behavior. The results show that the development of a cashless society is influenced by several factors, including convenience, economic efficiency, digital promotions, the characteristics of the millennial generation, and the integration of the digital ecosystem. On the other hand, digital payment systems also provide positive impacts such as increasing monetary system efficiency, transaction transparency, and financial inclusion. However, the convenience of transactions and promotional incentives may also increase impulsive buying behavior and consumerism. Therefore, the development of digital payment systems needs to be balanced with financial literacy to ensure responsible and rational financial behavior.